2013
DOI: 10.2147/ijn.s39232
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic effect of nanobased formulation of rivastigmine on rat model of Alzheimer's disease

Abstract: Background:To sustain the effect of rivastigmine, a hydrophilic cholinesterase inhibitor, nanobased formulations were prepared. The efficacy of the prepared rivastigmine liposomes (RLs) in comparison to rivastigmine solution (RS) was assessed in an aluminium chloride (AlCl 3 )-induced Alzheimer's model. Methods: Liposomes were prepared by lipid hydration (F1) and heating (F2) methods. Rats were treated with either RS or RLs (1 mg/kg/day) concomitantly with AlCl 3 (50 mg/kg/day). Results:The study showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 65 publications
1
51
0
Order By: Relevance
“…For AD, 26 full-text article reviews were performed, and 12 studies were included for their fulfillment of inclusion criteria ( Figure 3, Table 3). 80,[83][84][85][86][87][88][89][90][91][92][93][94][95] For PD, 19 full-text articles were reviewed, and eight articles had all the requisites to be considered here ( Figure 3, Table 3). [96][97][98][99][100][101][102][103] Unfortunately, for Huntington's disease, just one full article was analyzed and this article did not show any outcome of interest for this disease, and for this reason was not included here ( Figure 3).…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…For AD, 26 full-text article reviews were performed, and 12 studies were included for their fulfillment of inclusion criteria ( Figure 3, Table 3). 80,[83][84][85][86][87][88][89][90][91][92][93][94][95] For PD, 19 full-text articles were reviewed, and eight articles had all the requisites to be considered here ( Figure 3, Table 3). [96][97][98][99][100][101][102][103] Unfortunately, for Huntington's disease, just one full article was analyzed and this article did not show any outcome of interest for this disease, and for this reason was not included here ( Figure 3).…”
Section: Data Extractionmentioning
confidence: 99%
“…It would thus be desirable to develop new formulations to avoid these side effects, and all studies proved that the use of liposomes was a good strategy in the treatment of AD. 80,86,[90][91][92]111 Intranasal delivery of rivastigmine or galantamine liposomes has been shown to be a viable and effective route to improve drug bioavailability for brain drug targeting. 80,90,92 Intranasal delivery was also used as a successful approach for delivery of liposomes containing quercetin, which has antioxidant properties.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably impaired in AD are memory and language; however, other features include impairment in learning, attention, time perception, and planning (Buck et al, 1997;Coubard et al, 2011;O'Brien et al, 2009). Studies in animal models have identified numerous interventions that have demonstrated potential to attenuate some of the cognitive deficits associated with AD, (Abd-El-Fattah et al, 2014;Eketjall et al, 2013;Ismail et al, 2013;Liu et al, 2014;Long et al, 2013;Nagakura et al, 2013;Sierksma et al, 2013). Unfortunately, many of these interventions have not been proven effective in humans (Day et al, 2008;Franco & CedazoMinguez, 2014;Zeiss, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Though the rivastigmine solution significantly attenuated AChE activity, rivastigmine-loaded liposomes succeeded in normalizing AChE. 38 The delivery of liposomes to the brain can be attained via the intranasal route to overcome the BBB, 169,281,282 and liposomes can cross the BBB by transport lipid-mediated free diffusion or lipid-mediated endocytosis. 283 Rivastigmineloaded liposomes were prepared using the lipid hydration method for delivery into the brain via the intranasal route.…”
mentioning
confidence: 99%